Heat Efficiency Improvement of Ethanolamine Plant from Ethylene Oxide and Ammonia Through Heat Integration Analysis Using Pinch Technology - Vierina Putri Anindya; Irfan Mulyana; Jessi Pritiwara; Fajar Septiawan (Journal of Vocational Studies on Applied Research, 2026)
This study evaluates the impact of pinch analysis on energy efficiency in the preliminary design of an ethanolamine production plant using ethylene oxide and ammonia. The objective is to quantify reductions in external energy demand and to assess the feasibility of heat integration at the early design stage. Pinch analysis was conducted using process stream data derived from mass and energy balances, followed by composite curve construction, pinch point identification, and Heat Exchanger Network (HEN) synthesis using HINT software. The results show a significant reduction in both hot and cold utility requirements after heat integration, with internal heat recovery dominated by the reactor effluent and hot streams prior to distillation. The identified pinch temperature divides the process into distinct regions, enforcing strict utility placement and eliminating cross-pinch heat transfer. Maximum Energy Recovery (MER) analysis indicates substantial potential for internal heat utilization, directly translating into lower specific energy consumption and reduced utility costs. The synthesized HEN meets minimum energy targets while remaining thermodynamically feasible for preliminary plant design. Overall, the application of pinch technology demonstrates a strong and quantifiable impact on improving energy efficiency and provides a robust basis for energy-conscious decision-making in ethanolamine plant pre-design.